The Annunciation from the Monastery of Caleruega (Burgos): contextualisation in the Late Middle Ages of the Iberian Peninsula - Tomás Ibáñez Palomo (Anales de Historia del Arte, 2015)
The Annunciation from the Monastery of Santo Domingo of Caleruega, founded by Alfonso X the Wise, has remained virtually forgotten by the Spanish historiography. Isolated behind the walls of the cloister, the sculpture group presents a particularity that hasn’t been properly analyzed for too long: the Virgin is pregnant. The amount of recorded examples of the same nature shows that this kind of representations was common in some kingdoms of the Iberian Peninsula during the Late Middle Ages. From an essentially iconographic perspective, but without giving up further approaches, this paper provides an in-depth study on the singularity of the Annunciation from Caleruega. At the same time, it becomes the starting point for a comprehensive analysis of this variant of the Angelic Salutation.